The politics of possibility : risk and security beyond probability - Amoore, Louise (Duke University Press, 2013)
Dissects the post 9/11 symbiosis between the state and private security firms, and its basis: the conviction that uncertainties-devastation by terrorist attack, financial market collapse-must be discerned and preempted, however unlikely they may be.